KONSEP-KONSEP DASAR SUPERVISI PEMBELAJARAN - Reresi, Marsianus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2017)
This article is meant to provide some important topics in conection with conceptual investigation concerning academic supervision on study activity. The central subject we want to consider in tihis article is: “what is meant by academic supervision?” Academic supervision is a series of activities, by which the teacher is lent a hand to develop his ability to execute the practice of study activity on behalf of the teacher’s profesionalism.